FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marchel, Reyno; Kanti, Annisa (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
The purpose of this study is to obtain empirical evidence and analyze the effect of the independent variable on the dependent variable. The independent variables used in this study are firm size, firm age, independent board of commissioners, audit committee, sales growth, and leverage. While the dependent variable in this study is tax avoidance. The object of research used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2018-2020. The number of samples in this study were 60 companies with a total of 180 data. The method used in this research is purposive sampling method and this study uses multiple regression analysis to test the hypothesis. The result of this research is that sales growth has an effect on tax avoidance. Meanwhile, firm size, firm age, independent board of commissioners, audit committee, and leverage have no effect on tax avoidance.Keywords: Audit Committee; Company Age; Company Size; Independent Board of Commissioners; Leverage; Sales Growth; Tax Avoidance